2022
DOI: 10.1021/acs.biochem.2c00245
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Glues: The Adhesive Connecting Targeted Protein Degradation to the Clinic

Abstract: Targeted protein degradation is a rapidly exploding drug discovery strategy that uses small molecules to recruit disease-causing proteins for rapid destruction mainly via the ubiquitin–proteasome pathway. It shows great potential for treating diseases such as cancer and infectious, inflammatory, and neurodegenerative diseases, especially for those with “undruggable” pathogenic protein targets. With the recent rise of the “molecular glue” type of protein degraders, which tighten and simplify the connection of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 113 publications
0
46
0
Order By: Relevance
“…A plethora of excellent review articles on molecular glues and the complexes they stabilize have been published in the recent years, each focusing on a slightly different aspect of the topic, with the majority of them focusing on the discovery history, mechanism of action, and design strategy. [28][29][30][31][32][33][34][35][36][37] This review seeks to compile and analyze the current, published molecular glue ternary complex structures with the aim of identifying and quantifying any structural requirements for PPIs that are induced by molecular glues, as well as surveying the best computational methods to predict potential 'gluable' interfaces. To gain a general understanding of the molecular glue-induced PPI (MG-PPI), all molecular glue-induced complexes are considered, regardless of whether the molecular glue is a degrader.…”
Section: Jaeki Minmentioning
confidence: 99%
“…A plethora of excellent review articles on molecular glues and the complexes they stabilize have been published in the recent years, each focusing on a slightly different aspect of the topic, with the majority of them focusing on the discovery history, mechanism of action, and design strategy. [28][29][30][31][32][33][34][35][36][37] This review seeks to compile and analyze the current, published molecular glue ternary complex structures with the aim of identifying and quantifying any structural requirements for PPIs that are induced by molecular glues, as well as surveying the best computational methods to predict potential 'gluable' interfaces. To gain a general understanding of the molecular glue-induced PPI (MG-PPI), all molecular glue-induced complexes are considered, regardless of whether the molecular glue is a degrader.…”
Section: Jaeki Minmentioning
confidence: 99%
“…Among ACC patients, 3/15 (20%) achieved PR and 10/15 (67%) had SD. Notably, a previous phase 2 study of everolimus alone in 34 R/M ACC patients reported no objective responses [ 88 ], suggesting that lenalidomide (and other molecular glues which act through ubiquitin E3 ligases) may have activity in ACC [ 89 ].…”
Section: Systemic Agents For Recurrent/metastatic Accmentioning
confidence: 99%
“…Meanwhile, this may lead to possible limitations such as a "permanent" occupancy of the DUB that may in uence the DUB's function and prevent recycling of the DUB. In comparison, molecular glues are typically small chemical molecules that act on the interface between the target protein and the degradation machinery to trigger ternary complex formation 9 . They do not have separate chemical moieties interacting with each of the two proteins and the linker connecting the two moieties.…”
Section: Introductionmentioning
confidence: 99%
“…They do not have separate chemical moieties interacting with each of the two proteins and the linker connecting the two moieties. Thus, they are usually smaller and more druglike than chimeric compounds 9 . Therefore, molecular glues may exhibit advantages over DUBTACs in certain aspects.…”
Section: Introductionmentioning
confidence: 99%